Dampak Zakat Produktif dalam Pengembangan UMKM Masyarakat Kota Bima: Studi Kasus BAZNAS Kota Bima - Ardillah, Wulan Rekah; Muh. Yunan Putra; Muhammad Rasyad Al Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the impact of productive zakat on the development of MSMEs in the Bima City Community. The MSME actors referred to in this study are members of independent business groups in the National Zakat Agency (BAZNAS) of Bima City. This study is a field research using a qualitative approach with a case study strategy. Data collection techniques use observation techniques, interviews and direct documentation to the objects concerned. The data validity technique uses triangulation. The results of this study indicate that the productive zakat program provided by the National Zakat Agency (BAZNAS) of Bima City empowers mustahik by providing business capital, training skills, and providing assistance. So that mustahik (MSME actors) achieve financial independence and improve their standard of living in a sustainable manner. The positive impact of productive zakat is very broad, mustahik who were previously trapped in poverty, slowly rose with their growing businesses. Their income increased, new jobs were created, and the family's standard of living was raised. Then the productive zakat of BAZNAS Bima City has a great impact on MSMEs in the Bima City community, including opening up business opportunities for MSME actors, reactivating MSMEs whose businesses previously experienced a decline in Bima City and increasing the creativity of MSME actors in Bima City.